Application in fixed bed systems of adsorbents obtained from commercial activated carbon onto dyes solution - Muhammad Isa Mohd Ghazali (Penerbit Universiti Malaysia Perlis, 2011)
The sorption of two reactive dyes, namely Remazol Brilliant Blue and Orange G Pure, on activated carbon, has been studied. Three effects on adsorption of dye by activated carbon had been studies which are flow rate of dye when entered the column (5, 10, 15 ml/min) when bed height and initial concentration are constant (15 cm and 200 mg/l), initial concentration of dye (100, 200, 300 mg/l) with bed height (15 cm) and flow rate (5 ml/min) and bed height (10, 15, 20 cm) with constant flow rate (5 ml/min) and initial concentration (200mg/l). The removal of dye was faster in initial stages, gradually decreasing pattern and became constant after equilibrium was achieved. The initial dye concentration of the effluent is important since a given mass of adsorbent can only adsorb a fixed point amount of dye. Therefore, the more concentrated dyes, the smaller is the volume of effluent that a fixed mass. Effect of initial dye concentration in the inlet flow is one of the limitation factors and main process variables. The column experiments using activated carbon showed that adsorption efficiency increases with increase in the influent concentration and bed depth and decreases with increasing flow rate. The results suggest the highest bed height (10cm), lowest flow rate (5ml/min) and lowest initial dye concentration (100mg/l) provide in the most favorable outcome.